Vestigial appendicular skeletons in the African and Malagasy skink species Feylinia grandisquamis, Melanoseps ater, Grandidierina lineata and Voeltzkowia mira. Issue 1 (2nd January 2016) - Liniewski, Rachel; Stanley, Shane; Andrade, Julia; Senter, Phil
Abstract: Vestigial appendicular skeletons are present but have not previously been described and illustrated in the skink species Feylinia grandisquamis and Melanoseps ater . Vestigial appendicular skeletons have been described and illustrated in only one specimen of Grandidierina lineata and in a small sample of Voeltzkowia mira . Here we report a radiographic study of the appendicular skeletons of these four species. The pectoral girdle includes a vestigial clavicle in F. grandisquamis ; a vestigial scapulocoracoid and sternum in M. ater ; a vestigial scapulocoracoid, interclavicle and sternum, with or without a clavicle, in G. lineata ; and a clavicle and scapulocoracoid in one specimen of V. mira . In all four species the pelvic girdle includes an ilium and a puboischium. No midline contact is present between the left and right puboischium, and visible forking into a distinct pubis and ischium is present only in V. mira . The only discernible limb vestiges are humeri in V. mira .